2018
DOI: 10.1007/s10212-018-0378-9
|View full text |Cite
|
Sign up to set email alerts
|

Policy impact of PISA on mathematics education: the case of Norway

Abstract: This article addresses the policy implications of participation in international large-scale assessments (ILSAs), particularly the Programme for International Student Assessment (PISA), and the ways in which such implications might influence mathematics education. Taking Norway as a special case, this discussion focuses on insights into teaching, learning and assessment practices that can be inferred from the PISA study, and how participation in ILSAs has contributed to educational policy and even changed poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
0
17
0
2
Order By: Relevance
“…Such efforts might not take into account the cultural context of national educational systems. Analyses by Baird et al (2016) and Nortvedt (2018) have indicated that the national context influences policy decisions to a large extent.…”
Section: Policy Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such efforts might not take into account the cultural context of national educational systems. Analyses by Baird et al (2016) and Nortvedt (2018) have indicated that the national context influences policy decisions to a large extent.…”
Section: Policy Issuesmentioning
confidence: 99%
“…A key issue discussed in the research literature concerns the use of assessment data for policy development (Lin et al this issue;Nortvedt 2018) and whether existing assessment practices provide the information that stakeholders need to make informed decisions (Gaber et al 2012). This issue points to the potential consequences linked to the use of assessment data to inform decisions, since (1) more than one stakeholder is often involved and (2) the potential for misinterpretation always exists.…”
Section: Policy Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…A natural point of departure for reviewing the teachers' formal qualifications in Norway and Sweden can be traced back to an important phenomenon known as the PISA shock in 2001 (Elstad, Nortvedt, & Turmo, 2009;Haugsbakk, 2013;Lundström, 2015;Tveit, 2013). Norwegian students produced results on the PISA 2001 that were so far below expectations that the Norwegian Minister of Education compared it with the failure to bring home any medals from the Winter Olympics (Elstad et al, 2009;Nortvedt, 2018;Tveit, 2013). Following the PISA shock in 2001, Norway implemented several policy changes, including reforming the National Curriculum for Grades 1-13 called the "Knowledge Promotion" and introducing a National Quality Assessment System that implemented national tests alongside participation in other ILSA studies, like TIMSS 2 (for more details, see Elstad et al, 2009).…”
Section: Teacher Qualifications In Norway and Swedenmentioning
confidence: 99%
“…Politically, lower than desired performance has the potential to legitimise increased government involvement in re-orientating mathematics education policies (Dossey & Wu, 2013;Ertl, 2006;Takayama, 2008), although PISA results may also be used to validate existing policy proposals (Nortvedt, 2018). As Dossey and Wu (2013) noted, "the very existence of rankings provided by assessments such as the … OECD studies provide a perceived base of scientific rationality for policy proposals and their public explanations" (p. 1019).…”
Section: Introductionmentioning
confidence: 99%